Short Food Supply Chain Network for Small-Scale Rural Tilapia Aquaculturists in Guerrero and Oaxaca, Mexico - Catalán Dibene, César Gioberti (2025)
Small-scale rural tilapia aquaculturists (SSRTAs) operating in the states of Guerrero and Oaxaca, Mexico, are excluded from conventional trade channels. Short food supply chains (SFSCs) offer an alternative marketing model that suits the characteristics of these small production units, such as low output volumes and isolated locations. The objective of this study is to characterize SSRTAs based on the localities where they operate and, through network analysis, to identify the types of SFSCs they are involved in. The goal is to provide evidence of how these chains function and contribute to the discussion on whether they represent a viable option for improving SSRTAs’ incomes. The data used for the analysis and application of the network methodology were provided directly by 29 tilapia aquaculturists—nine located in Guerrero and 20 in Oaxaca—across 28 localities, mainly in rural areas of both states.